La cité au bout du fil le téléphone à Montréal de 1879 à 1930 - Poitras, Claire (Presses de l'Université de Montréal, 2000)
Keywords: Bell Canada; Téléphone

Steamboat connections : Montreal to Upper Canada, 1816-1843 - Mackey, Frank (McGill-Queen's University Press, 2000)
"In Steamboat Connections Frank Mackey gives us a narrative account of the first twenty-five years of steam navigation along the St. Lawrence and Ottawa Rivers. Relying on a wealth of primary archival sources, Mackey focuses on the development of steamer traffic from 1816 - when the foundations were laid for the first stage and steamboat line between Montreal and Upper Canada - to the early 1840s - when locks, canals, innovations, and human daring conquered the rapids on those rivers and allowed for navigation between Montreal and the Great Lakes. He shows how, starting in 1841, small steamers ran "the circuit" - down the rapids of the St. Lawrence to Montreal and then back up to Kingston and other Great Lakes ports via the Ottawa River and the Rideau Canal." "Mackey introduces the entrepreneurs who forged this important link between Montreal and the nation's interior and chronicles the course of their industry, correcting previous misinterpretations. He sheds light not only on steamboats but also on the social, commercial, and geographical development they made possible. He shows that the history of this country, a land with vast expanses and a harsh climate, cannot be fully appreciated without looking at the different modes of transportation that made it possible."--BOOK JACKET.
Keywords: Navigation

Housing Revitalization in Montreal: Are Condominium Conversions a Sustainable Alternative? - Swaby, Chantelle Simone (Université de Montréal, 2000)
Keywords: Logement

Les publicités à succès selon le concours du Publicité-Club de Montréal - Allagui, Ilhem (Université de Montréal, 2000)
Keywords: Publicité

Les trains de banlieue et l'aménagement du territoire dans la région de Montréal - Quirion, Étienne (Université de Montréal, 2000)
Keywords: Banlieue; Transport en commun

Brasseurs, brasseries et activités brassicoles dans la plaine de Montréal, 1788-1852 - Morin, Stéphane (Université du Québec à Montréal, 2000)
Keywords: Brasserie

Impact des améliorations locatives sur la valeur d'un immeuble: le cas de Place Montréal Trust - Boilly, Jacques (Université du Québec à Montréal, 2000)
Keywords: Centres commerciaux

Le comportement de consommation artistique et culturel des groupes ethniques à Montréal, le cas des Portugais, des Maghrébins et des Italiens - Paiement, Isabelle (Université du Québec à Montréal, 2000)
Keywords: Italiens; Maghrébins; Portugais

Les étapes de la science économique au Québec: démarrage, construction et maturité - Fortin, Pierre (L'Actualité économique, 2000)
Keywords: Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal

L'impact d'un casino sur l'économie urbaine: application au Casino de Montréal - Trépanier, Fannie (École des hautes études commerciales de Montréal, 2000)
Keywords: Île Notre-Dame

Unilingues ou bilingues? Les Montréalais sur le marché du travail en 1901 - MacKinnon, Mary (L'Actualité économique, 2000)
Cette étude utilise un échantillon du Recensement canadien de 1901 pour estimer le taux de rendement du bilinguisme pour les hommes de langue maternelle anglaise et française à Montréal. Le bilinguisme a profité aux anglophones et aux francophones; et la prime au bilinguisme pour les deux groupes semble quelque peu supérieure à celle des années 1960. En 1901, un francophone bilingue qui savait lire et écrire gagnait en moyenne à peu près le même revenu qu’un anglophone unilingue catholique. Les anglophones protestants bilingues obtenaient les revenus moyens les plus élevés.
Keywords: Bilinguisme; Travail

Bruce Price, and his Montreal Train Stations - Dandurand, Kevin (Université Concordia, 2000)
Keywords: Gare Viger; Gare Windsor; Gares

Montreal’s Place in the North American Economy - Kresl, Peter Karl; Proulx, Pierre-Paul (American Review of Canadian Studies, 2000)

L'autoroute urbaine à Montréal: la cicatrice et sa réparation - Sénécal, Gilles; Archambault, Julie; Hamel, Pierre J. (Les espaces dégradés: contraintes et conquêtes, 2000)
Keywords: Autoroutes

Manufacturing Montreal. The Making of an Industrial Landscape, 1850-1930 - Lewis, Robert D. (John Hopkins University Press, 2000)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Résidence et liens de parenté des artisans de Montréal en 1741 - Groulx, François; Gauthier, Jean-Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2000)
Keywords: Artisans; Arts sacrés; Famille

Les techniques et le commerce de la tannerie à Montréal au XVIIIe siècle - Perrier, Jocelyne (Scientia Canadensis, 2000)
Keywords: Artisans; Marchands; Tannerie

Nouveau regard sur les relations judéo-québécoises: le commerce comme lieu d’échanges, Montréal 1900-1940 - Taschereau, Sylvie (Juifs et Canadiens français dans la société québécoise, 2000)
Keywords: Juifs

La réduction de gaz à effet de serre et les transports urbains des personnes à Montréal - Gandulfo, Mónica (Université de Sherbrooke, 2000)
Keywords: Automobile; Climat; Transport en commun

Histoire de la librairie au Québec - Roy, Fernande (Leméac, 2000)
Keywords: Librairie

L’héroïsation dans le discours épistolaire et l’autobiographie: le cas de Pierre du Calvet (1735-1786) - Saint-Germain, Annie (Université du Québec à Montréal, 2000)
Keywords: Du Calvet, Pierre; Marchands

The Evolution of Organizational Identity: A Discursive Study - Chreim, Samia (École des hautes études commerciales de Montréal, 2000)